A criminalização da pobreza nos processos de acolhimento institucional infanto-juvenil - Gross, Léia Lediane (Universidade Federal do Tocantins, 2021)
The present Work of Conclusion of Specialization Course in Social Work and Social Policy holds a debate about the criminalization of poverty in institutional reception procedures, as a protective measure provided for in the Statute of the Child and Adolescent (ECA). The question that instigates us, therefore, lies in the ambiguity expressed by the protection measure that is effected through institutional reception, we seek to carry out the analysis of the deontology of the reception policy and its overlap with sociability, in order to structure the conceptual basis so that we could understand whether such a measure is capable of making social rights viable or ends up being a more control strategy, criminalizing families in asituation of poverty, considering that hospitalization in asylum institutions was the primary way in which society and the State sought to ensure assistance to Brazilian children and young people, establishing in Brazil a true "culture of institutionalization", thus constituting a historical option of childcare in the country, especially that of families living in poverty. Concerning the methodological aspects it is recorded that the theoretical reference used for research and analysis of the results was based on the critical-historical social theory, supported by the foundations of the praxis philosophy, the research had as reference the foundations of the bibliographical research, with a bias of qualitative. It is concluded that the process of institutionalization of children and adolescents, which in the thesis would have the function of mitigating the variables existing in the various forms of expression and manifestation of the "social question", which include those subject to such procedure, in the end, further determines the extension of these expressions, in a clear retributive effect, consigning the logic of punishment and criminalization of poverty.